2011
DOI: 10.1097/shk.0b013e3182205cbc
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils, Not Monocyte/Macrophages, are the Major Splenic Source of Postburn IL-10

Abstract: Burn induces myeloid-derived suppressor cells (MDSCs), a heterogeneous population of immature polymorphonuclear neutrophils (PMNs) and monocytes, which protect against infection. Previous work from our laboratory demonstrated that inflammatory monocytes (iMos) were the major MDSC source of TNF-α in the postburn spleen, and we hypothesized that they were also the major source of postburn IL-10. To test this hypothesis, we examined cytokine production by postburn CCR2 knockout (KO) mice, which have fewer iMos th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…These anti-inflammatory macrophages (M2) and neutrophils (N2) secrete high amounts of IL-10, a potent anti-inflammatory cytokine (5,7,22,24), and have been implicated in the dysfunctional immune response to burn injury. Excessive IL-10 has been shown to be detrimental for bacterial clearance by attenuating protective proinflammatory cytokines, such as IL-12 (25,26,28), and in our prior report elevated IL-10 was associated with increased ALI risk after burn and inhalation injury (14).…”
Section: Discussionmentioning
confidence: 99%
“…These anti-inflammatory macrophages (M2) and neutrophils (N2) secrete high amounts of IL-10, a potent anti-inflammatory cytokine (5,7,22,24), and have been implicated in the dysfunctional immune response to burn injury. Excessive IL-10 has been shown to be detrimental for bacterial clearance by attenuating protective proinflammatory cytokines, such as IL-12 (25,26,28), and in our prior report elevated IL-10 was associated with increased ALI risk after burn and inhalation injury (14).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that increased IL-6 levels have been associated with elevated cancer risk, and also been found to be a prognostic factor for several cancer types [24]. IL-10 is emerging as a key cytokine mediating the suppressive function of neutrophils, and dampening tumor-specific immune surveillance [25,26,27]. IL-4Rα-STAT6 signaling could induce the production of ARG1 by MDSCs [28].…”
Section: Discussionmentioning
confidence: 99%
“…MDSCs, unlike terminally differentiated macrophages, express low concentrations of MHC-II and CD80/CD86, making them poor antigen presenting cells 51 . However, these MDSCs, unlike terminally differentiated macrophages and monocytes after sepsis or trauma, produce large amounts of IL-10, TNFα, RANTES, MCP1, SDF-1 and MIP1α 51,89, 90, 91 . These cells also consume large quantities of arginine, producing NO, reactive oxygen species, and peroxynitrites that are both proinflammatory and immunosuppressive.…”
Section: Emergency Myelopoiesis Drives Persistent Immunosuppresion Anmentioning
confidence: 99%